2011
DOI: 10.1007/s10096-011-1399-3
|View full text |Cite
|
Sign up to set email alerts
|

Molecular characterization of Streptococcus pneumoniae invasive serotype 19A isolates from adults in two Spanish regions (1994–2009)

Abstract: From 1994 to 2009, the incidence of invasive serotype 19A pneumococci isolated from adults in Barcelona and San Sebastian almost doubled every 4 years. Genotyping of the 167 invasive isolates studied showed serotype 19A to be highly heterogeneous, with 35 different sequence types (STs) and a different clonal structure in each region and time period. Multiresistance, defined as non-susceptibility to three or more antimicrobials, was found in 86 (51.5%) isolates. The most frequent ST was the multidrug-resistant … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
9
0

Year Published

2012
2012
2021
2021

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 14 publications
(9 citation statements)
references
References 14 publications
0
9
0
Order By: Relevance
“…In Asia and the USA, ST320 has been described as a highly prevalent clone showing a worldwide distribution and rapid and broad spread among children. To date, ST320 has had limited diffusion among the adult Spanish population [32].…”
Section: Discussionmentioning
confidence: 99%
“…In Asia and the USA, ST320 has been described as a highly prevalent clone showing a worldwide distribution and rapid and broad spread among children. To date, ST320 has had limited diffusion among the adult Spanish population [32].…”
Section: Discussionmentioning
confidence: 99%
“…[ 37 38 39 40 ] Since the identification of MDR S. pneumoniae (resistant to >3 different antimicrobial classes) in the 1970s, its prevalence has steadily increased in many countries. [ 41 42 43 ] In 1988, a report from Saudi Arabia showed that all S. pneumoniae isolates were sensitive to penicillin and vancomycin, but 65% were resistant to trimethoprim-sulfamethoxazole. [ 32 ] A newer study reporting childhood pneumococcal bacteremia in Riyadh showed that 20.4% of the isolates were penicillin-resistant and 22% were MDR.…”
Section: Epidemiologymentioning
confidence: 99%
“…This CC has been identified in the United States, although its relative contribution to serotype 19A replacement has been modest. In southern Europe, however, expansion of CC276 has been found to dominate the serotype 19A increase, with moderate contribution from CC199 (1,8,9).…”
mentioning
confidence: 99%
“…CC320 was not identified in the United States prior to vaccine introduction. CC320 has also been identified in France and Spain (8,9) and was found to dominate the pre-PCV7 increase of serotype 19A in South Korea (3). In Norway, however, a single isolate of ST320 was identified in 2004, before the introduction of PCV7.…”
mentioning
confidence: 99%